2011
DOI: 10.2119/molmed.2010.00243
|View full text |Cite
|
Sign up to set email alerts
|

GNMT Expression Increases Hepatic Folate Contents and Folate-Dependent Methionine Synthase-Mediated Homocysteine Remethylation

Abstract: Glycine N-methyltransferase (GNMT) is a major hepatic enzyme that converts S-adenosylmethionine to S-adenosylhomocysteine while generating sarcosine from glycine, hence it can regulate mediating methyl group availability in mammalian cells. GNMT is also a major hepatic folate binding protein that binds to, and, subsequently, may be inhibited by 5-methyltetrafolate. GNMT is commonly diminished in human hepatoma; yet its role in cellular folate metabolism, in tumorigenesis and antifolate therapies, is not unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 39 publications
2
42
0
Order By: Relevance
“…Glycine N-methyltransferase (GNMT) acts as an essential component that influences synthesis of sarcosine [2932]. Synthesis of GNMT is controlled by the same gene named GNMT .…”
Section: Molecular Biology Of Sarcosinementioning
confidence: 99%
“…Glycine N-methyltransferase (GNMT) acts as an essential component that influences synthesis of sarcosine [2932]. Synthesis of GNMT is controlled by the same gene named GNMT .…”
Section: Molecular Biology Of Sarcosinementioning
confidence: 99%
“…Among all forms of folates, the 5‐methyl tetrahydrofolate (5‐methyl‐THF) is the most abundant . Although GNMT binds to 5‐methyl‐THF and can subsequently be inhibited by 5‐methyl‐THF, we have demonstrated that GNMT‐bound‐5‐methyl‐THF is bioavailable for methylfolate‐dependent homocysteine remethylation . Mice with Gnmt deletion have poor folate status; and cells without GNMT expression exhibited more cytotoxicity in response to antifolate drugs.…”
mentioning
confidence: 85%
“…The Gnmt knockout mouse model was established by gene‐targeting disruption as described previously . Nullizygotes (Gnmt −/− ) had undetectable GNMT protein expression, and the heterozygotes (Gnmt +/− ) had ∼50% of GNMT expression compared to their wild‐type) littermates (Gnmt +/+ ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In study II, we used an amino acid-defined diet to carefully control dietary supplies of amino acid and vitamins. This approach is also helpful when we need to compare results among different studies on folate and vitamin metabolism (Wang et al, 2011). In study II, mice were fed a modified Clifford/Koury amino acid-defined rodent diet containing the recommended daily allowance for vitamin B 6 for rodents (7 mg/Kg pyriodoxine-HCl) (Dyets).…”
Section: Methodsmentioning
confidence: 99%